Emotions manifested by school adolescents in the COVID-19 pandemic (Research, Society and Development, 2021)
Faced with the pandemic by COVID-19, the main occupation of adolescents, studies, has undergone an abrupt change with social isolation and the suspension of face-to-face classes, which can cause emotional suffering for this group. Objective: To identify emotional manifestations of school adolescents in the face of the COVID pandemic 19 and emotional management strategies adopted by them. Method: Exploratory-descriptive study, carried out from the University-Primary Care-School articulation. A Google Forms questionnaire was sent, via the school platform, to adolescent high school students from a public school in the city of Niterói-RJ. After a month of making the questionnaire available, 15 students answered. For data analysis, the appropriate statistics and absolute and percentage frequencies were calculated. The study was approved by the Ethics and Research Committee - Opinion No. 3,671,594. Results: The main emotions expressed by school adolescents in the face of Pandemic were tiredness (63.6%), sadness (45.5%), longing for school and friends (45.5%), lack of face-to-face classes (18.2 %), indifference (27.3%) and depression (9.1%). Positive emotions such as joy (27.3%) were also identified. Everyone reports that they had infected relatives, friends, neighbors or acquaintances and 36.4% knew someone who died. The data showed that all adolescents are connected to a virtual network and point out as emotional management strategies implemented by themselves: music (63.6%), social networks (54.5%), chatting with friends (45.5%), games / games (36.4%), church and dating (27.3%), sports, school, films and series (9.1%). Conclusions: School adolescents are experiencing emotional disorders as a result of the pandemic and have implemented emotional management strategies on their own.